Boric Acid Preservation of Urine Samples. Issue 5653 (10th May 1969) - Porter, I. A.; Brodie, J.
Abstract : Comparison of the results of bacteriological culture and microscopic examination of urine samples transported over a distance by the dip-inoculum transport medium, ice-box, and boric acid preservation with "natural" urine specimens showed that the last, in a final concentration of 1·8%, gives satisfactory preservation.